The effect of equilibration time on semen freezing of local swamp buffalo (Bubalus bubalis) with combination extender of lactose and glycerol - KARTINI ERIANI; NISA SARI; MEUTIA IHDINA; ROSNIZAR ROSNIZAR (Smujo International, 2017)
Eriani K, Sari N, Ihdina M, Rosnizar. 2017. The effect of equilibration time on semen freezing of local swamp buffalo (Bubalus bubalis) with combination extender of lactose and glycerol. Nusantara Bioscience 9: 77-82. This study was to determine the different time of equilibration on semen of swamp buffalo (Bubalus bubalis) which was diluted by adding Tris-Egg Yolk extender of lactose and glycerol cryoprotectant combination. Fresh sperm of the swamp buffalo (B. bubalis) was diluted by using Tris-Egg Yolk extender of lactose cryoprotectants combination 0 mM (L0), 60 mM (L60), 120 mM (L120) and glycerol 3% (G3), 5% (G5), 7% (G7) with the equilibration of 2,5, 3, and 4 hours. The parameter used in this study was the percentage of sperm motility and live treatment. The results of the 2.5-hour equilibration with a combination of cryoprotectants L60G7 showed the best quality in all parameters. The results of the 3-hour equilibration with combination of cryoprotectants L60G7 showed the best quality in all parameters whereas the best quality in all parameters in 4-hour equilibration was the combination of cryoprotectants L120G7.